Nauczyciel edukacji wczesnoszkolnej kreatorem dialogu międzykulturowego - Żmijewska, Ewa (Nauczyciel wczesnej edukacji wobec zmian społeczno-kulturowych, 2016)
The main duty of early school teachers who work in multicultural society is to promote intercultural dialogue. The very tenet of inclusive communication, i.e. communication which reconciles different cultures, is that it develops what we know as a third culture. Practical classes with second-form pupils in a primary school were used to create an educational environment promoting intercultural dialogue. This offered a new experience to both pupils and university students. The project involved a series of four integrated classes based on excerpts selected from “Spotkania z Innymi” by P.P. Grzybowski. Both subjects involved in the study drew on popular knowledge and their respective experiences to address issues such as fear of the Other, stereotypes and subculture, illness and loneliness, and racial and ethnic differences.